Ageing of polyimide under thermal stress: Relaxational effects and charge transport. (April 2021) - Henri, V.; Dantras, E.; Lacabanne, C.; Koliatene, F.; Trebosc, C.
Highlights: Polyimide films were aged under thermal stress. Dynamic Mechanical Analysis revealed a two-step degradation mechanism of Polyimide. The modification of the diffusion behaviour pointed out an acceleration of the molecular mobility. Broadband dielectric spectroscopy shows a modification of the charge transport mechanism associated with the degradation. Abstract: Polyimide is one of the most used polymer for electrical insulation in severe environment. For future aircrafts, polymer electrical insulation will be exposed to thermal constraints that can affect its physicochemical structure. Effects of thermal ageing are studied through their impact on the relaxational behaviour. Thermal degradation impairs first the aromatic entities and lately the carbonyls. It is responsible for the strong acceleration of mobility observed for both localised β and γ relaxation modes. Both DMA and swelling test exhibit an acceleration of localized molecular mobility. However, as the local mobility is accelerated, the increase in heterogeneities visible through the evolution of the MWS polarisation brings up to light a change in the charge transport mechanism. The chain scission degradation mechanism, leads to a decrease of the density of deep traps. It explains the evolution of both the value of DC conductivity and its activation energy upon ageing.